2020
DOI: 10.1061/(asce)me.1943-5479.0000823
|View full text |Cite
|
Sign up to set email alerts
|

Recoverability Modeling of Power Distribution Systems Using Accelerated Life Models: Case of Power Cut due to Extreme Weather Events in Norway

Abstract: Today's societies rely on electrical power distribution systems. Recent weather events have illustrated that the loss of such service can lead to severe consequences for societies and stakeholders. Hence, in order to reduce the impact of such extreme events on infrastructure systems and to limit the associated losses, it is crucial to design infrastructure that can bounce back and recover rapidly after disruptions (i.e. to be resilient). In this regard, it is vital to have knowledge of technical, organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…In general, based on the nature of collected data, if there is an unobservable risk factor, the frailty model is appropriate; otherwise, the PHM and its extension can be used for reliability analysis. In the presence of p 1 time-independent risk factors, (z) , and p 2 time-dependent risk factors, ( z(t) ), the frailty model takes the following form [ 33 , 34 ]: where λ 0 (t) is the baseline hazard rate, the function captures the effect of observed risk factors, and α is the frailty. The α > 1 are said to be frailer for reasons left unexplained by the observed risk factors and will have an increased risk of failure, while items with α < 1 are less frail; hence, given a specific observed risk factor pattern, they tend to be more reliable.…”
Section: The Methodology: Spare-part Prediction Using Frailty Modementioning
confidence: 99%
See 3 more Smart Citations
“…In general, based on the nature of collected data, if there is an unobservable risk factor, the frailty model is appropriate; otherwise, the PHM and its extension can be used for reliability analysis. In the presence of p 1 time-independent risk factors, (z) , and p 2 time-dependent risk factors, ( z(t) ), the frailty model takes the following form [ 33 , 34 ]: where λ 0 (t) is the baseline hazard rate, the function captures the effect of observed risk factors, and α is the frailty. The α > 1 are said to be frailer for reasons left unexplained by the observed risk factors and will have an increased risk of failure, while items with α < 1 are less frail; hence, given a specific observed risk factor pattern, they tend to be more reliable.…”
Section: The Methodology: Spare-part Prediction Using Frailty Modementioning
confidence: 99%
“…As Eq ( 2 ) shows, frailty represents one or more unobserved risk factors’ cumulative effect. Given the relationship between the hazard rate and the reliability functions, it can be shown that the conditional reliability function, R ( t ; z ; z ( t )| α ), can be written as [ 33 , 34 ]: …”
Section: The Methodology: Spare-part Prediction Using Frailty Modementioning
confidence: 99%
See 2 more Smart Citations
“…To be more specific, these two indexes can identify which components in an infrastructure network are vulnerable to disruption in advance and thus enable taking immediate restoration actions in the aftermath of a disaster. Rød et al (2020a) acknowledged the significance of unobserved technical, organizational, internal, and external factors, which can affect the recovery process of power distribution systems. The authors developed an accelerated failure time model to consider the effect of such otherwise neglected factors along with traditionally observed ones in simulating the recovery time of disrupted power distribution systems in Norway.…”
mentioning
confidence: 99%